1988
DOI: 10.1288/00005537-198808000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin ototoxicity in guinea pigs with special reference to toxic effects in the stria vascularis

Abstract: The toxic effects of cisplatin (cis-diamminedichloroplatinum [II]) on the organ of Corti are well established. Few and conflicting data on this drug's effects on the stria vascularis exist. The present study presents animal experiments on the toxic effects of cisplatin in the stria vascularis and in the organ of Corti. Cisplatin-induced toxicity in albino and pigmented guinea pigs was evaluated morphologically and functionally, using light and transmission electron microscopy as well as auditory brainstem-evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…Morphologically, edema formation in the SV appeared during the early phase of degeneration after CDDP treatment, followed by severe atrophy during the late phase. The time course of morphological changes of the SV observed in this study was similar to that observed in previous studies using systemic CDDP application [3][4][5]. TUNEL assays revealed induction of apoptotic cell death in the SV after CDDP treatment.…”
Section: Cell Death Model For the Svsupporting
confidence: 88%
See 1 more Smart Citation
“…Morphologically, edema formation in the SV appeared during the early phase of degeneration after CDDP treatment, followed by severe atrophy during the late phase. The time course of morphological changes of the SV observed in this study was similar to that observed in previous studies using systemic CDDP application [3][4][5]. TUNEL assays revealed induction of apoptotic cell death in the SV after CDDP treatment.…”
Section: Cell Death Model For the Svsupporting
confidence: 88%
“…The stria vascularis (SV) is known as a primary site of CDDP ototoxicity. In the SV, it has been shown that marginal cells are especially vulnerable to CDDP-induced damage [3,4]. In addition, it has been demonstrated that there is a high correlation between marginal cell damage and hearing loss [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many beneficial features of cisplatin, serious side effects are nephrotoxicity, neurotoxicity, and ototoxicity. In regard to ototoxicity, it is believed that cisplatin selectively damages the outer hair cells within the organ of Corti, spiral ganglion cells and cells within the stria vascularis [2,3]. Ototoxicity can occur anytime from hours to days after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although cisplatin is one of the most potent OHC toxins known [Anniko and Sobin, 1986], it may also cause hearing loss by affecting other inner ear structures, such as the stria vascularis [Nakai et al, 1982;Tange and Vuzevski, 1984;Kohn et al, 1988;Saito and Aran, 1994;Watanabe et al, 2002]. Indeed, a major decrease in the endocochlear potential (EP), implying stria vascularis dysfunction, has been observed early after the occurrence of cisplatin-induced threshold shifts [Klis et al, 2000[Klis et al, , 2002Tsukasaki et al, 2000].…”
Section: Introductionmentioning
confidence: 99%